Association between the rs342293 polymorphism and adverse cardiac events in patients undergoing percutaneous coronary intervention - Siller-Matula, Jolanta M.; Arbesu, Iciar; Jilma, Bernd; Maurer, Gerald; Lang, Irene M.; Mannhalter, Christine (Thrombosis and Haemostasis, 2014)
The single nucleotide polymorphism (SNP) rs342293 has been shown to influence platelet number and mean platelet volume (MPV). We investigated the association between the rs342293 polymorphism and cardiovascular outcome in a prospective cohort study. The rs342293 polymorphism was analysed in 404 patients with coronary artery disease undergoing percutaneous coronary intervention. The rates of cardiac adverse events were recorded during two years of follow-up. The polymorphism was associated with MPV (median 10.1 fL, interquartile range [IQR]: 9.6 to 10.6 in patients with the CC-allele vs 10.4 fL, IQR: 9.9 to 11.1 in G>C SNP carriers; p<0.001), but not with platelet count. Survival analysis indicated that carriers of the rs342293 G variant had a substantially higher risk to develop cardiac adverse events compared with wild type carriers during two years of follow-up (33% vs 22%; adjusted hazard ratio = 1.63, 95% confidence interval = 1.06–2.52, p=0.027). The rs342293 SNP could explain 2.9% of the variability in MPV (p=0.01). In conclusion, patients undergoing coronary stenting who carry the G-variant of the rs342293 SNP which is associated with larger MPV are at higher risk for adverse cardiovascular outcome.
Keywords: Platelet aggregation; polymorphism; genetic; outcome assessment (healthcare); platelet count; myocardial Infarction